A brief review on integration between wireless sensor networks and Cloud. (15th April 2021) - Liazid, Hidaya; Lehsaini, Mohamed
Summary: Wireless sensor networks (WSNs) are an interconnection between hundreds to thousands of geographically distributed sensor nodes often called motes. WSNs are deployed in various fields for collecting data; they are used in healthcare monitoring, weather service, civil and military applications, and so on. WSNs are faced with many challenges due to their lack of computational resources, restrained storage capacities, and limited energy resources. The apparition of Cloud computing technology with its many advantages led the idea of integration between these two technologies. In this article, we will present an overview of works related to the interconnection between WSNs to the Cloud. After analyzing the contents of the published works, we established their classification according to the subjects treated. Four items are therefore selected, namely storage and computation, security, application and finally integration for Internet of Things (IoT). This brief review of the literature shows that the development of WSNs‐Cloud interconnection solves the problem of minimizing energy consumption at the sensor level, the problem of data storage, as well as the problem of access to the medium.